Segmentasi Food Safety Knowledge and Practice Ibu Rumah Tangga di Kabupaten Sleman - Ninik Sri Rahayu (Unisia, 2008)
This article proposes to elaborate on the consumer segmentation, especially housewives, in Sleman Region, based on the level of their food safety knowledge and practices. House- wives have been chosen to be samples based on the reason that food shopping activities in most family units have been done by this group. Using cluster analysis, this research has revealed three segments of consumers, namely those having food safety knowledge and practices who are high (37%0), medium (34%), and low (29%). This article recom- mends that relevant institutions be concerned to educate target groups, especially those who are high risk, in order for them to avoid consuming food which are harmful for their health. Keywords: consumer, segment, housewives, food safety knowledge and practice